European Yearbook on Human Rights 2020 / edited by Philip Czech [and four others]. - Czech, Philip (Intersentia, 2020)
In light of the 30th anniversary of the UN Convention on the Rights of the Child in 2019, the twelfth edition of the European Yearbook on Human Rights is dedicated to the rights of the child. In their contributions, renowned scholars, emerging voices and practitioners provide a cross-section of the progress and gaps with regard to the protection of children. Topics include children deprived of their liberty, compulsory adoption and children's rights to participate in public debates on climate change, to name but a few. Besides the thematic focus on the rights of the child, this edition includes valuable insights from the European Court of Human Rights and the OSCE on the current challenges for the protection of human rights in Europe. Contributions focusing on the human rights implications of artificial intelligence, state sovereignty and gender identities raise awareness of the complexities of human rights protection and stimulate debate and further research in the field. At a time of an unprecedented global health crisis which has had widespread economic, social, humanitarian and human rights dimensions, the European Yearbook on Human Rights continues to provide a platform to address existing gaps in the systems designed to protect human rights and to bring forward suggestions to remedy identified weaknesses. Philip Czech is a researcher at the Austrian Institute for Human Rights, University of Salzburg and editor of the Newsletter Menschenrechte. Lisa Heschl is a post-doctoral research and teaching fellow at the European Training and Research Centre for Human Rights and Democracy, University of Graz. Karin Lukas is a senior researcher and Head of Department at the Ludwig Boltzmann Institute of Human Rights. Manfred Nowak is Secretary General of the Global Campus of Human Rights, Venice and Professor of International Human Rights, University of Vienna. Gerd Oberleitner is UNESCO Chair in Human Rights and Human Security and Director of the European Training and Research Centre for Human Rights and Democracy.